1996
DOI: 10.1038/ki.1996.338
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides for ICAM-1 attenuate reperfusion injury and renal failure in the rat

Abstract: The leukocyte adhesion molecule ICAM-1 is implicated in ischemic renal reperfusion injury. We tested the utility of an ICAM-1 antisense oligodeoxyribonucleotide (ODN) with lipofectin, six hours prior to 30 minutes of bilateral renal ischemia in the rat. We measured ICAM-1 expression by immunohistochemistry and Western blot. Our antisense ODN showed a specific ICAM-1 surface expression inhibition in vitro. We then assessed ICAM-1 expression, leukocyte infiltration, serum creatinine, serum urea concentration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
85
2
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 31 publications
5
85
2
2
Order By: Relevance
“…In response to I/R, ECs increase the expression of cell adhesion molecules, such as vascular cell adhesion molecule 1 (Vcam1) and Icam1, which recruit and activate circulating inflammatory cells in the kidneys. [3][4][5][6][7] The results of previous studies have demonstrated that administration of blocking antibodies against Vcam1 or Icam1 ameliorated renal I/R injury in rodents. [3][4][5] Likewise, antisense oligonucleotides for Icam1 attenuated ischemic AKI in rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to I/R, ECs increase the expression of cell adhesion molecules, such as vascular cell adhesion molecule 1 (Vcam1) and Icam1, which recruit and activate circulating inflammatory cells in the kidneys. [3][4][5][6][7] The results of previous studies have demonstrated that administration of blocking antibodies against Vcam1 or Icam1 ameliorated renal I/R injury in rodents. [3][4][5] Likewise, antisense oligonucleotides for Icam1 attenuated ischemic AKI in rats.…”
mentioning
confidence: 99%
“…[3][4][5] Likewise, antisense oligonucleotides for Icam1 attenuated ischemic AKI in rats. 6 Moreover, Kelly et al 7 showed that Icam1-deficient mice were protected from I/R injury to the kidneys. These results suggest that regulation of cell adhesion molecules is critical for controlling ischemic AKI.…”
mentioning
confidence: 99%
“…Leukocyte adhesion molecules seem to facilitate polymorphonuclear neutrophils recruitment during reperfusion, being implicated as mediators of renal IRI (5,6). Complementary studies using mAb, antisense oligonucleotides, or gene "knockout" indicate that blockade of ␤2 integrins and/or intercellular adhesion molecule-1 attenuates IRI in some experimental models (7)(8)(9)(10)(11)(12)(13). Furthermore, it was proposed recently that T cells might also mediate IRI through the interaction with renal tubular epithelial cells (14).…”
mentioning
confidence: 99%
“…Adhesion molecules expressed on cell surfaces mediate specific cell-cell interactions in embryogenesis, histogenesis, immune responses, and inflammatory reactions (Galkina and Ley, 2007). Several studies using different anti-ICAM-1 strategies have shown attenuation of functional impairment and histological changes during acute renal failure (Kelly et al, 1991(Kelly et al, , 1996Haller et al, 1996). During this study, increased expression of ICAM-1 in interstitial area and in tubules was observed.…”
Section: Discussionmentioning
confidence: 66%